RELATIONSHIP BETWEEN NUTRITION KNOWLEDGE AND AEROBIC FITNESS IN YOUNG GYMNASTS - Nazhif Gifari; Rachmanida Nuzrina; Mury Kuswari; Nabila Tri Hutami; Ayu Ghalda (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
This study aimed to analyze the nutrition knowledge, nutritional status, body composition, nutrient intake and physical fitness of young gymnasts. The study used a cross-sectional design with 20 subjects comprising rhythmic and artistic gymnasts in Raden Inten, Jakarta. Nutritional status and body composition were measured using anthropometric measurements, macronutrient and micronutrient intakes were measured with 3x24-h food recall, physical fitness was measured using the bleep test (20m shuttle run), and nutrition knowledge was assessed using questionnaires consisting of 30 questions on macronutrients, micronutrients and water. The results indicated that the gymnasts (n=20, 13.7±2.1 y.o, 37.8±8.2 kg and 147.3±10 cm) generally had a fairly good nutrition knowledge score (73.2%); i.e. 10 people in the good nutrition-knowledge group and 10 people in the poor nutrition-knowledge group. The majority of the macronutrient and micronutrient intakes were below the nutritional requirements, in both the good and poor nutrition-knowledge groups. The nutrition knowledge scores were low for hydration-related knowledge (66%), while the scores for macronutrient and micronutrient knowledge were 73.8% and 84.2%, respectively. This study found that nutrition knowledge had a positive correlation with physical fitness (p<0.05). A sports nutrition-related education intervention is needed for those gymnasts that still have poor nutrition knowledge. Sports nutrition knowledge needs to be provided for athletes and coaches so that athletes' intakes meet their nutritional requirements in order to maximise their performance.